Sirtuin 1 in osteoarthritis: Perspectives on regulating glucose metabolism - Zhihao Liao; Xuepei Cai; Yifan Zheng; Jiayu Lin; Xia Yang; Weiyin Lin; Ying Zhang; Xin He; Chufeng Liu (Pharmacological Research, 2024)
Osteoarthritis (OA) is a degenerative disease characterised by articular cartilage destruction, and its complex aetiology contributes to suboptimal clinical treatment outcomes. A close association exists between glucose metabolism dysregulation and OA pathogenesis. Owing to the unique environment of low oxygen and glucose concentrations, chondrocytes rely heavily on their glycolytic capacity, exhibiting distinct spatiotemporal differences. However, under pathological stimulation, chondrocytes undergo excessive glycolytic activity while mitochondrial respiration and other branches of glucose metabolism are compromised. This metabolic change induces cartilage degeneration by reprogramming the inflammatory responses. Sirtuins, a highly conserved family of nicotinamide adenine dinucleotide (NAD+)-dependent deacetylases, regulate glucose metabolism in response to energy fluctuations in different cellular compartments，alleviating metabolic stress. SIRT1, the most extensively studied sirtuin, participates in maintaining glucose homeostasis in almost all key metabolic tissues. While actively contributing to the OA progression and displaying diverse biological effects in cartilage protection, SIRT1’s role in regulating glucose metabolism in chondrocytes has not received sufficient attention. This review focuses on discussing the beneficial role of SIRT1 in OA progression from a metabolic regulation perspective based on elucidating the primary characteristics of chondrocyte glucose metabolism. We also summarise the potential mechanisms and therapeutic strategies targeting SIRT1 in chondrocytes to guide clinical practice and explore novel therapeutic directions.